Description of a new species of the Loxerebia saxicola (Oberthür, 1876)-complex from Guizhou, Southwest China (Lepidoptera: Nymphalidae: Satyrinae) - Wang, Xue-Jian; Lang, Song-Yun (Zootaxa, 2024)
In this paper, a new species of the Loxerebia saxicola (Oberthür, 1876)-complex, viz. L. zangkena Lang & Wang sp. nov., is described from Guizhou province, Southwest China.